Possibilities of Using Process-Based ERP Systems in Sustainable Management of the Organization's Resources - Tomasz TUREK (Communications of International Proceedings, 2021)
The article presents the potential of ERP systems to support sustainable resource management of organizations. The first part presents the evolution of IT systems from MRP to ERP solutions. Next, attention was paid to the process approach in management. This approach requires adapting business information systems to BPM requirements.  In this context three types of ERP systems can be distinguished: non-process systems, quasi-process systems and process-based systems. An example of a process-based system is Macrologic Merit ERP, which is described in the article. New capabilities of process-based ERP systems seem to be an ideal solution for sustainable manufacturing. These systems have a set of tools that can be useful in designing, measuring and developing manufacturing processes.
Keywords: Process-Based ERP; Resource Management; Sustainable Management; Process Management